Customer Engagement of the Coffee Shop during Covid-19 Pandemic: Study on Anomali Coffee’s Instagram - Devita, Marliani; Kania, Dessy (Jobmark: Journal of Branding and Marketing Communication, 2022)
The COVID-19 virus pandemic has triggered the #ngopidirumah movement that is echoed on social media by local coffee shops in maintaining relationships with consumers by adjusting the consumer's lifestyle during quarantine at home. Anomali Coffee also runs the #ngopidirumah movement through Instagram in order to build online Customer Engagement. The purpose of this study was to find out how the Customer Engagement that was built by Anomali Coffee on Instagram during the COVID-19 pandemic. The literature review used is Customer Engagement, Lifestyle, Social Media and Instagram. The research method used is qualitative with a case study approach. Sources of data obtained through in-depth interviews, online observation and digital documentation. The results showed that in building Customer Engagement in the #ngopidirumah movement, Anomali Coffee has reached all stages of Consumption, Curation, and Creation. At the Collaboration stage, Anomali Coffee produces Indirect Collaboration with consumers in building coffee consumption activities at home, but not to form a solid community.Customer Engagement, Social Media, Instagram, Anomali Coffee, #ngopidirumah Movement